Ecology of Anopheles darlingi, the Primary Malaria Vector in the Americas and Current Nongenetic Methods of Vector Control - Conn, Jan E.; Ribolla, Paulo E. [UNESP] (Elsevier, 2016)
Anopheles darlingi is the primary malaria vector throughout most of its distribution from Mexico to Argentina. Depending on the environment, it displays a range of behaviors: anthropophily, opportunism, endo-exophagy, and endo-exophily. It readily colonizes anthropogenic sites and is susceptible to Plasmodium vivax and Plasmodium falciparum. Anopheles darlingi displays moderate variability and significant population structure between Central America plus northwestern South America; and the Amazon. Within the Amazon region, it consists of multiple clusters or putative species, each with partial barriers to gene flow. The other significant malaria vector in northern South America and the Caribbean is Anopheles albimanus, consisting of three distinct lineages with limited gene flow among them. Because most Neotropical vectors are opportunistic, exophagic, and exophilic, the vector control mainstays of long-lasting insecticide-treated nets and indoor residual spraying are not effective alone, and integrated vector control methods, tailored to specific transmission hot spots, will be needed to improve the probability of malaria elimination.
Keywords: Anopheles albimanus; Anopheles darlingi; Behavior; Ecology; Laboratory colonization; Malaria; Plasmodium; Vector control